Are overwhelmed health systems an inevitable consequence of covid-19? Experiences from China, Thailand, and New York State - Tangcharoensathien, Viroj; Bassett, Mary T; Meng, Qingyue; Mills, Anne (BMJ (Online), 2021)
Drawing on international experiences, Viroj Tangcharoensathien and colleagues argue that immediate extensive action to contain local transmission of new infectious diseases protects health systems from being overwhelmed